2012
DOI: 10.1186/1758-907x-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Target gene expression levels and competition between transfected and endogenous microRNAs are strong confounding factors in microRNA high-throughput experiments

Abstract: BackgroundMicroRNA (miRNA) target genes tend to have relatively long and conserved 3' untranslated regions (UTRs), but to what degree these characteristics contribute to miRNA targeting is poorly understood. Different high-throughput experiments have, for example, shown that miRNAs preferentially regulate genes with both short and long 3' UTRs and that target site conservation is both important and irrelevant for miRNA targeting.ResultsWe have analyzed several gene context-dependent features, including 3' UTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Among exo-miRNA target genes, the genes with short 3′ UTRs were more efficiently downregulated than those with long 3′ UTRs by the transfection of exo-miRNAs (Figure 5A), consistent with the previous report [31]. In this analysis, we used the fold change values of exo-miRNA targets with 3′ UTRs complementary to seed sequence of either one strand of exo-miRNA duplex: let-7b-5p, miR-1, miR-21-5p, miR-22-5p, miR-28-5p, miR-30c-5p, miR-186-5p, miR-199b-5p, miR-200b-3p, miR-330-5p, miR-335-5p, miR-346, miR-466, miR-574-5p and miR-3126-5p.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Among exo-miRNA target genes, the genes with short 3′ UTRs were more efficiently downregulated than those with long 3′ UTRs by the transfection of exo-miRNAs (Figure 5A), consistent with the previous report [31]. In this analysis, we used the fold change values of exo-miRNA targets with 3′ UTRs complementary to seed sequence of either one strand of exo-miRNA duplex: let-7b-5p, miR-1, miR-21-5p, miR-22-5p, miR-28-5p, miR-30c-5p, miR-186-5p, miR-199b-5p, miR-200b-3p, miR-330-5p, miR-335-5p, miR-346, miR-466, miR-574-5p and miR-3126-5p.…”
Section: Resultssupporting
confidence: 93%
“…The results showed good agreement with the previous study [31]. In contrast, the endo-miRNA targets with low expression levels in the normal conditions were uncovered to be intensively upregulated by the exo-miRNA transfection, and those with high expression levels were not upregulated efficiently (Figure 6B).…”
Section: Resultssupporting
confidence: 92%
“…Possible mechanisms could include the following: other miRs, such as miR-20b 58 and 519c, 59 triggering reverse effects upon HIF-1a may contribute to the hypoxia response in a complicated network involving the HIF-1a/Fhl-1 pathway; miR-206 may switch its regulating function in a quantitydependent manner in response to hypoxia; and when miR-206 mimics were applied, competition and saturation effects from endogenous miR-206 could have been involved in the process. 60,61 These effects would be expected to relieve repression of the HIF-1a from other endogenous miRs. The fact that miR-206 is involved in hypoxia-induced PH and that its expression changes frequently in different microenvironments suggests that multiple modes of transcriptional regulation exist for this miR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sinha et al reported that genes promoters with high CpG content were more often targeted by miRNAs 12 . Saito and Saetrom also discussed the relationships between miRNAmediated gene regulation and various features of target genes, but they did not consider the methylation status of target gene promoters 13 . Although the study of Su et al represents the first evidence of a direct link between promoter methylation and miRNA regulation, the biological significance of their findings is not clear.…”
Section: Introductionmentioning
confidence: 99%